Feminist Popular Education and Community Arts/Crafts: The Case for New Directions - Darlene E. Clover; Joyce Stalker; Laurie McGauley (Adult Education Research Conference, 2004)
Through the lens of a feminist cultural organisation in Sudbury, Ontario, this paper extends the notion of feminist popular education by exploring the activist and aesthetic-pedagogical dimensions of women’s community arts/crafts practices.